2018
DOI: 10.1002/lsm.22827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10 efficient protocols for photodynamic therapy of actinic keratosis: How relevant are effective light dose and local damage in predicting the complete response rate at 3 months?

Abstract: Protocols that achieve high complete response rates at 3 months and low pain scores should be preferred regardless of the effective light dose and local damage. Lasers Surg. Med. 50:576-589, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
1
19
1
Order By: Relevance
“…The authors concluded that protocols that achieve high complete response rates at 3 months and low pain scores should be preferred regardless of the effective light dose and local damage. 16 Our protocol with half-time red light conventional illumination obtains lower pain scores with similar response to complete time of illumination. To our knowledge, this form of perform PDT in patient has not been published.…”
Section: Although Daylight Also Include Blue and Green Light (Visiblementioning
confidence: 73%
See 1 more Smart Citation
“…The authors concluded that protocols that achieve high complete response rates at 3 months and low pain scores should be preferred regardless of the effective light dose and local damage. 16 Our protocol with half-time red light conventional illumination obtains lower pain scores with similar response to complete time of illumination. To our knowledge, this form of perform PDT in patient has not been published.…”
Section: Although Daylight Also Include Blue and Green Light (Visiblementioning
confidence: 73%
“…In this way, a recent study based in a mathematical model compared 10 different protocols of illumination, including conventional red light PDT, daylight PDT and blue light. The authors concluded that protocols that achieve high complete response rates at 3 months and low pain scores should be preferred regardless of the effective light dose and local damage . Our protocol with half‐time red light conventional illumination obtains lower pain scores with similar response to complete time of illumination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these two PpIX-weighted metrics are increasingly used in most recent papers. 10,[17][18][19] Assuming spectral irradiances with constant shapes but different amplitudes, the ratio between two PpIX-weighted irradiances is equal to the ratio between the two corresponding irradiances. As a result, irradiances could be converted into PpIX-weighted irradiances by applying the rule of three to data reported in a recent study.…”
Section: Irradiance and Ppix-weighted Irradiancementioning
confidence: 99%
“…As a result, irradiances could be converted into PpIX-weighted irradiances by applying the rule of three to data reported in a recent study. 19 Computed to the spectral irradiance measured from the Aktilite CL 128 by O'Gorman et al, 20 these data consist of an irradiance of 85.39 mW/cm 2 and its associated PpIX-weighted irradiance of 1.44 mW/cm 2 . The significance level was set at a two-sided alpha level of 0.05.…”
Section: Irradiance and Ppix-weighted Irradiancementioning
confidence: 99%
“…Therefore, with the aid of computer modelling, doses may be estimated below the skin surface, including the impact that wavelength-dependent attenuation of daylight at such depths may have on PpIX-effective light dose. Vignion-Dewale et al used mathematical modelling to demonstrate local damage in tissue for ten different PDT modalities and found that DPDT may have as much local damage (singlet oxygen generation) and PpIX-effective light dose delivered as conventional PDT regimens at a depth of 100 µm [28]. Actinic keratoses are superficial and are thus equally treatable with either less penetrating blue or more deeply penetrating red light during PDT [29].…”
mentioning
confidence: 99%